Centralização e transporte do canal radicular utilizando instrumentos de glide path com diferentes cinemáticas: estudo ex vivo - Miró, Gabriela Behne (2019)
The objective of this study was to compare through computed microtomography, the ability of the WaveOne Gold Primary system and glide path instruments with different kinematics to maintain the original position of vestibular medium channels of the first upper molars, as well as the volume variation, angular deflection and cyclic and torsional fatigue resistance. Thirty-six teeth were selected and included in the study teeth with curvature degree between 10° and 30° and mean length of 20mm. The selected teeth were randomly divided into 5 experimental groups PG (Pro Glider), WOGG (WaveOne Gold Glider), PWOG (WaveOne Gold Primary), PG + PWOG (Pro Glider + WaveOne Gold Primary) and WOGG + PWOG (WaveOne Gold Glider + WaveOne Gold Primary). The analysis with computed microtomography was performed to evaluate the centralization and linear transport at 1, 3, 5 and 7 mm from the foramen. The root canal volume variation, angular deflection and cyclic and torsional fatigue of the instruments used were also evaluated. After the results were obtained, they were divided into two manuscripts. As results, it was observed when comparing the glide path instruments (PG and WOGG) with the PWOG in terms of transport and centralization, that in the levels of 1mm and 5mm, there was no significant difference between the groups (p>0,05). However, at levels of 3mm and 7mm, the PWOG group was statistically different from the PG and WOGG groups in root canal transport (P<0,05). Comparing the preparation instrument (PWOG) associated or not to the glide path instruments (PG+PWOG and WOGG+PWOG), there was a statistically significant difference between the PWOG group and the WOGG+PWOG group in the transport of the root canal at 7mm from the apical foramen (P<0,05). The group WOGG+PWOG in the apical region (1mm) was the one that kept the channel more centralized and was statistically different from the other groups (P<0,05). There was no statistically significant difference between the groups for volume variation, angular deflection and cyclic and torsional fatigue of the instruments evaluated. With this it can be concluded that the pre-enlargement with glide path instruments, independent of the kinematics employed, decreases the linear transport of the root canal, did not interfere with the mechanical properties however, does not change the ability to maintain centralisation with WOGG.